„HERETYKOM BYŁ BARZO SRÓG, […] TAK IŻ GO MŁOTEM HERETYKÓW ZWALI”: ŚWIĘCI JAKO INSPIRATORZY WALKI Z HETERODOKSJĄ I STRAŻNICY JEDNOŚCI KOŚCIOŁA (NA PRZYKŁADZIE ŻYWOTÓW ŚWIĘTYCH PIOTRA SKARGI) - Cybulska-Bohuszewicz, Ewa (Prace Polonistyczne, 2021)
The article examines Żywoty świętych (The Lives of Saints) by Piotr Skarga and the protagonists’ fight against those whom the author calls the “new heretics”. Written in Polish and rich in persuasive artistic devices that influence the reader’s imagination, Skarga’s book turned out to be an extremely effective tool of re-Catholicization in the Counter-Reformation era. The author vividly describes the stories of God’s chosen ones, showing them as active agents in the eternal battle with Satan, in the text embodied by the “dissenters”. By the power of parenesis and allegoresis, even figures as distant as Moses or the Desert Fathers prefigure Skarga’s model of a saint: the Soldier of Christ who protects the unity of the Church.